CULTURE SHOCK SANTRI ASAL KANGEAN DI PONDOK PESANTREN SALAFIYAH SYAFI’IYAH SUKOREJO SITUBONDO - Moch. Nuril Anwar; Edy Supriyono (Maddah : Jurnal Komunikasi dan Konseling Islam, 2024)
This article discusses the culture shock of students from Kangean at the Salafiyah Syafi'iyah Islamic Boarding School in Sukorejo, Situbondo. Culture shock is a situation where a person is not familiar with the social habits of a new culture, so that an individual cannot display behavior that is in accordance with the rules in the new environment. The students from Kangean, who are from the island of Madura, are students who tend to be tough in character. But he will love people who don't hurt him. It is important to know about the community's background in terms of area and geographical conditions because people from the beach have a different character from people from the mountains. From the beach every day they fight the waves, feel the hot atmosphere with the hot sun so that psychologically they are associated with a reactive attitude towards something. When entering a new environment, namely an Islamic boarding school in Java, it was interesting to see how this Satri from Kangean communicated with peo ple of a different culture, and reached the level of culture shock. This research uses a descriptive qualitative research method. A method for examining the status of a group of people, an object, a condition, a system of thought, or a class of events in t he present. The aim of this descriptive research is to create a systematic, factual and accurate description, picture or painting of the facts, characteristics and relationships between the phenomena being investigated. The results of this research are tha t in the adaptation process, Kangean students go through phases of cultural adaptation, such as the honeymoon phase where students from Kangean experience a move so that they will feel happy because they are in a new atmosphere, the Disintegration phase of culture shock where students from Kangean will experience a the feeling of discomfort caused by differences, then the adjustment phase (Reintegration) where the students from Kangean begin to open themselves up to cultural differences, then the Autonomy p hase (familiarity with the situation) phase where a person becomes increasingly able to adapt because he has passed the previous phases like his anxiety and restlessness can be accepted and he accepts all the differences that exist. And the last one is the Independence phase, a phase where they enjoy the existing differences and a person is more confident when faced with the rhythm of a new environment and existing challenges